Avaliação da resposta comportamental, morfofisiológica e produção de leite de cabras puras e mestiças da raça Saanen no semi-árido do Rio Grande do Norte - Furtado, Gil Dutra (2007)
Goat breeding in the state of Rio Grande do Norte, Brazil has promising economic possibilities, with the proper handling of the natural resources. The introduction of specialized animals has been one of the ways used to improve herd genetics and increase productivity. However, climate has been one of the regional factors that most interferes with the adaptation of the new genetic prevalence resulting from the introduction of exotic breeds, because in their country of origin, the air temperature during most of the year is lower than the animals body temperature. With this in mind, the aim of this study was to characterize behavioral, physiological and morphological profiles and milk production of female Saanen goats belonging to different genetic groups raised in the semi-arid region of Rio Grande do Norte in Northeast Brazil. The study was conducted in the city of Lages (5° 42 00 S and 36° 14 41 W). We used 25 lactating female Saanen goats, distributed into 3 genetic groups: 5 purebred animals, 11 three-quarter bred and 9 half-bred. Behavioral observations were made over three consecutive days in the months of August and September, between 09:00 and 11:30h, when the animals were grazing. Physiological and meteorological data were recorded in the last three days of June, July, August and September at 05:00h and at 16:00h. In the semi-intensive breeding system, the animals from different genetic groups were similar in both field behavior and physiological response patterns. Although the purebred goats had longer hair, they did not show symptoms of thermal discomfort. Their white hair helped to reflect the short wavelength rays and thus eliminate those at the longer wave lengths. We concluded that the animals raised in the semi-intensive milk production system in this study seem to have adapted to the climatic conditions of the semi-arid region of Rio Grande do Norte, Brazil